2011
DOI: 10.1039/c0sc00644k
|View full text |Cite
|
Sign up to set email alerts
|

Solvation dynamics of surface-trapped electrons at NH3 and D2O crystallites adsorbed on metals: from femtosecond to minute timescales

Abstract: The creation and stabilization of localized, low-energy electrons is investigated in polar molecular environments. We create such excess electrons in excited states in ice and ammonia crystallites adsorbed on metal surfaces and observe their relaxation in real time using time-resolved photoelectron spectroscopy. The observed dynamics proceed up to minute timescales and are therefore slowed down considerably compared to ultrafast excited state relaxation in front of metal surfaces, which proceeds typically on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 49 publications
(93 reference statements)
0
27
0
Order By: Relevance
“…They thus broaden the concept of intrinsic polaron trapping to disordered wide gap oxides. Localization of excess electrons in deep states has so far been observed in a small number of systems, such as polar [56,57] and non-polar [58,59] liquids, ammonia and water ice and amorphous films on metal substrates [60][61][62], and alkali halide melts [49,50,63,64]. In the latter case, bipolarons facilitated by fluctuations in the melt have also been observed and calculated [49][50][51], although electron polarons do not form in alkali halide crystals.…”
mentioning
confidence: 88%
“…They thus broaden the concept of intrinsic polaron trapping to disordered wide gap oxides. Localization of excess electrons in deep states has so far been observed in a small number of systems, such as polar [56,57] and non-polar [58,59] liquids, ammonia and water ice and amorphous films on metal substrates [60][61][62], and alkali halide melts [49,50,63,64]. In the latter case, bipolarons facilitated by fluctuations in the melt have also been observed and calculated [49][50][51], although electron polarons do not form in alkali halide crystals.…”
mentioning
confidence: 88%
“…Previous ultrafast surface science investigations have shown that the dynamics of an electronic state in a molecular film can differ based on the molecular properties of the film, the electronic state localization, influence of the metal substrate, and molecular film thickness. 8,10,[27][28][29][30][31][32][33][34][35] The contrasting dynamics of electron localization in nonpolar n-heptane versus polar water and ammonia highlight the influence of the molecular properties of the film. In ultra-thin non-polar n-heptane layers on a Ag(111) surface, electron injection leads to the formation of small polarons that are self-trapped via the in-phase methylene rocking of n-heptane on an approximately 360 fs timescale.…”
Section: Introductionmentioning
confidence: 99%
“…4,36,37 In frozen water and ammonia, electrons form solvated electrons in pre-existing electron traps on ultrafast timescales. 28,31,34 Solvated electrons are electrons cooperatively supported by the dipole moments of the solvent and are typically described in a cavity or pseudo-cavity model. 38,39 For many electronic states near metal interfaces, recombination with the metal substrate is the primary decay mechanism that determines the electronic state lifetime.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,270,271,272 The processes that are anticipated to play a fundamental role in the electron dynamics at the interfaces are electron injection, localization, solvation and simultaneous back transfer to the metal. The simulation of this complex scheme is beyond the capabilities of the computational techniques that have been implemented so far.…”
mentioning
confidence: 99%